109 An rer of 1.05 to signify a maximum test underestimates peak vo2 in patients referred for heart transplantation. (6th June 2022) - Barnes, Joshua; Thomas, Max; Sylvester, Karl; Martinez, Luis
Abstract : Background: The most recent International Society for Heart Lung Transplantation (ISHLT) guidelines defines a maximal cardiopulmonary exercise test (CPET) as a respiratory exchange ratio (RER) of >1.05 with the achievement of anaerobic threshold (Mehra et al., 2016). Based off a maximal CPET, the ISHLT recommend a peak oxygen consumption (VO2peak) of ≤14 ml/min/kg for patient's intolerant of beta-blockers and ≤12 ml/min/kg in the presence of a beta-blocker for guiding heart transplantation listing. Recently, Thomas and Sylvester (2020) demonstrated that a RER of 1.05 underestimated peak VO2peak and would impact patients' risk stratification for surgery, or diagnostic outcomes. It is unknown whether this is true for patients with advanced heart failure referred for heart transplantation assessments. Methods: A retrospective analysis of patients with advanced heart failure that underwent a CPET as part of their heart transplant assessment between May 2019 and July 2021 was performed via cycle ergometry. Patients were included if they met all of the following: symptom-limited test, peak RER >1.15 and >6-minute test duration. Oxygen consumption (VO2), minute ventilation and heart rate were collected at RER's of 1.00, 1.05, 1.10, 1.15, 1.20 and peak-exercise. A Friedman test was used to compare data across all RER points, while independent t-tests were used to compare differences in data between specific RER's. Results: A CPET was performed in 151 patients, of which 59 patients met the inclusion criteria. Baseline characteristics can be seen in Table 1. VO2 (ml/min/kg) significantly increased as RER increased from 1.05 to peak (p<0.001) (Figure 1). Based on ISHLT guidelines for using VO2peak to guide heart transplantation listing, inappropriate referrals for heart transplantation would have occurred in 5%, 26%, 29% and 31% of patients when taking VO2 at an RER of 1.05 compared to 1.10, 1.15, 1.20 and peak RER, respectively. Conclusion: In our cohort of patients with advanced heart failure, VO2peak progressively increased in parallel to RER from 1.05 to peak. Using an RER of 1.05 to determine a maximal CPET in patients referred for heart transplantation will underestimate true peak VO2peak in a proportion of cases and may lead to inappropriate heart transplantation referrals. Conflict of Interest: None